ChemInform Abstract: Aminomethylation Reaction of ortho‐Pyridyl C—H Bonds Catalyzed by Group 3 Metal Triamido Complexes. Issue 27 (18th June 2015) - Nagae, Haruki; Shibata, Yu; Tsurugi, Hayato; Mashima, Kazushi
Abstract Complexes of either gadolinium or yttrium are found to be optimal in the reaction of pyridine derivatives and some analogous N‐heterocycles with unactivated imines.